Novel antimicrobial packaging film based on porous poly(lactic acid) nanofiber and polymeric coating for humidity-controlled release of thyme essential oil. (January 2021) - Min, Tiantian; Sun, Xiaoli; Yuan, Zhipeng; Zhou, Liping; Jiao, Xiangyu; Zha, Junwei; Zhu, Zhu; Wen, Yongqiang
Abstract: The objective of this work is to explore a new pathway to develop active packaging materials. Currently, controlled release materials have attracted considerable attention in food packaging applications. In this study, the thyme essential oil (TEO) was loaded in electrospinning porous poly(lactic acid) (PLA) nanofibers and coated with poly(vinyl alcohol)/poly(ethylene glycol) (PVA/PEG) blends for humidity-controlled TEO release. The images of scanning electron microscope displayed uniform pores distributed on the surface of PLA nanofibers. Water contact angle measurement indicated that PVA/PEG coating provided the packaging film with excellent hydrophilicity. ATR-FTIR spectral analysis supported the chemical composition of the films. The antibacterial activities of PLA/TEO/PVA/PEG films against Escherichia coli and Staphylococcus aureus reached ＞99%. Furthermore, the weight loss and firmness of strawberries packaged with this novel film were evaluated. Finally, the in vitro release behaviors of TEO were evaluated and the results demonstrated that the release rate could be controlled by adjusting the humidity (20% RH to 80% RH). Highlights: An innovative food packaging film based on porous PLA nanofibers was fabricated. Hydrophilic PVA/PEG used for humidity-controlled release of thyme essential oil. Porous structure of nanofibers improved the loading capacity of thyme essential oil. This novel packaging film prolonged the shelf life of strawberries. The humidity responsive system provided a new pathway for active packaging.